A Positive Attitude to Negate a False Positive Test Result: An Intern's Experience with COVID-19 - Vanessa N. Youmbi (University Library System, University of Pittsburgh, 2020)
I recount my experience as an intern in the Democratic Republic of Congo during the COVID-19 pandemic. I received a patient who was presumed to have COVID and was isolated. The first test result was a false positive, so I was discharged. Although I was not infected by COVID-19, I was adversely affected by it. The anxiety of waiting for test results and isolation are both mentally challenging. Also, COVID-related stigmatization is a serious complication of the disease. Targeted psychological interventions should prevent all three.